2009
DOI: 10.1016/j.bbmt.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Successful Prevention of Acute Graft-versus-Host Disease Using Low-Dose Antithymocyte Globulin after Mismatched, Unrelated, Hematopoietic Stem Cell Transplantation for Acute Myelogenous Leukemia

Abstract: In this study, we investigated the effects of low-dose antithymocyte globulin (ATG, thymoglobulin) in the prevention of acute graft-versus-host disease (aGVHD) in mismatched, unrelated hematopoietic stem cell transplantations (uHSCTs) in patients with the single disease entity of acute myelogenous leukemia (AML). Patients (n = 103) with a variable risk for AML who received uHSCTs from available Asian and Caucasian donors were enrolled. First, we compared HLA-matched (group 1, n = 54) and HLA-mismatched (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 19 publications
1
55
1
Order By: Relevance
“…The 5-year survival of the complete HLA identical cases was 79.1% ± 8.78%, and the 5-year survival of the HLA mismatched patients was 52.0% ± 10.3%. Our results are consistent with those reported by Kim [28] 2009 and Mohty [29] 2010 in HLA-MUR transplantation.…”
Section: Discussionsupporting
confidence: 83%
“…The 5-year survival of the complete HLA identical cases was 79.1% ± 8.78%, and the 5-year survival of the HLA mismatched patients was 52.0% ± 10.3%. Our results are consistent with those reported by Kim [28] 2009 and Mohty [29] 2010 in HLA-MUR transplantation.…”
Section: Discussionsupporting
confidence: 83%
“…[29][30][31][32] Administration of rabbit-anti-human T lymphocyte antibodies has been increasingly used by transplant programs because the antibodies can partially prevent aGVHD and cGVHD without impacting rates of relapse and non-EBV infections (except when used at a high dose, for example, 48 mg/kg thymoglobulin). 9,20,[33][34][35][36][37][38][39][40][41] Thus, our findings that in patients conditioned with rabbit-ATG, the PTLD occurrence is relatively high (8.1%) and that the vast majority of PTLD's occurring before day 100 are important. This suggests that monitoring EBV DNAemia in the first 100 days is warranted, together with preemptive (at the time of high/rising EBV DNAemia) or prompt (early in the course of PTLD) administration of rituximab- [42][43][44] or EBV-specific T lymphocytes.…”
Section: Discussionmentioning
confidence: 69%
“…10 The utility of pre-transplant ATG as part of GVHD prophylaxis in patients receiving URD transplants has been debated for many years, and while the use of ATG appears to reduce the incidence of GVHD, benefits in terms of OS are less clear. [11][12][13][14]19 Further, both the preparation and dose of ATG appear to be important determinants of its impact on post-transplant outcomes. For rabbit ATG (Thymoglobulin), an early multicenter prospective study conducted by the GITMO group suggested that while a dose of 15 mg/kg was associated with a significant reduction in the risk of severe (grades III-IV) GVHD, this benefit was counterbalanced by an increased risk of opportunistic infections, resulting in similar OS for ATG and placebo groups.…”
Section: Discussionmentioning
confidence: 99%